COVID-19 vaccination-associated anti-Jo-1 syndrome - Kushagra Gupta; Gauri Shankar Sharma; Ashok Kumar (Rheumatology, 2021)
Post-vaccination inflammatory myositis is a rare but known entity in the literature. We encountered a 46-year-old female patient, who presented with complains of fever, arthralgia, and weakness 1 week after taking the second dose of COVID-19 (Oxford-AstraZeneca) vaccine. On workup she had raised inflammatory markers, evidence of myositis on magnetic resonance imaging of thighs, and evidence of interstitial lung disease on high-resolution computed tomography of the chest. The patient was further found to be positive for anti-Jo-1 antibody. She was managed with steroids and methotrexate initially. She briefly developed pneumocystis pneumonia and recovered. She was later switched to mycophenolate mofetil and responded well. We report the first case of anti-Jo-1 syndrome reported following COVID-19 vaccination in the literature. Our aim is to sensitise the clinicians to such rare but occasionally life-threatening complications that may arise in the post-vaccination period.